2015
DOI: 10.1111/cdep.12111
|View full text |Cite
|
Sign up to set email alerts
|

The Autonomy‐Connection Challenge in Adolescent–Peer Relationships

Abstract: The world of peers presents a unique developmental challenge to adolescents—one that is likely to be linked to prior experiences within the family, affected by concurrent experiences with adults outside the family, and predictive of future mental and physical health. To negotiate relationships with peers successfully, adolescents must manage the challenge of connecting with peers while establishing autonomy regarding peer influences. Both the nature of this challenge and how it is handled are linked closely to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
53
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(55 citation statements)
references
References 53 publications
2
53
0
Order By: Relevance
“…Notwithstanding differences across age, gender and sites in the relative frequency and salience afforded to different types of stressors, a common thread appeared to be the broad developmental challenge of establishing an independent social identity. This struggle is characteristic of adolescence across cultures, as adolescents attempt to establish autonomy in their romantic and other peer relationships, educational/employment transitions and other life choices [26, 27]. Extensive research from the field of developmental psychopathology has shown that social challenges in adolescence operate within interacting ecological systems, which render differences in the experience of stress and coping according to an individual’s intrinsic characteristics, the immediate physical and social environment, and broader social, political and economic conditions [28].…”
Section: Discussionmentioning
confidence: 99%
“…Notwithstanding differences across age, gender and sites in the relative frequency and salience afforded to different types of stressors, a common thread appeared to be the broad developmental challenge of establishing an independent social identity. This struggle is characteristic of adolescence across cultures, as adolescents attempt to establish autonomy in their romantic and other peer relationships, educational/employment transitions and other life choices [26, 27]. Extensive research from the field of developmental psychopathology has shown that social challenges in adolescence operate within interacting ecological systems, which render differences in the experience of stress and coping according to an individual’s intrinsic characteristics, the immediate physical and social environment, and broader social, political and economic conditions [28].…”
Section: Discussionmentioning
confidence: 99%
“…Managing peer relationships is one of the most challenging and significant developmental tasks adolescents face (Allen and Loeb, 2015). Building solid relationships with peers appears crucial to healthy social development in adolescence (Allen and Loeb, 2015; Llorca et al, 2017a).…”
Section: Introductionmentioning
confidence: 99%
“…Developmental researchers have argued that there are benefits to high levels of agency during adolescence (Allen et al., 2002; Allen & Loeb, 2015). Specifically, Allen and Loeb (2015) argue that being able to advocate for one’s own point of view, feel comfortable voicing dissenting opinions, and act on one’s own beliefs, are important social skills adolescents should obtain to foster close interpersonal ties and avoid risk behaviors. Hence, there may be utility in considering how to foster connections to school without reducing agency.…”
Section: Discussionmentioning
confidence: 99%
“…Social goals are particularly relevant to adolescent development because forming and maintaining close bonds with peers, parents, role models, and schools represents an important task for this developmental time period (Allen & Loeb, 2015; Collins & Steinberg, 2006). Social goals are organized around a circumplex structure with two orthogonal dimensions representing agency (dominance/power/assertiveness) and communion (nurturance/affiliation) (Locke, 2003; Wright, Pincus, & Lenzenweger, 2012).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation